2010
DOI: 10.1021/jp1036603
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Deletion Effects of Human Survivin on Dimerization and Binding to Smac/DIABLO in Vitro

Abstract: Survivin, as an apoptosis suppressor, exists as a homodimer interfacing at the N-terminal portion (residues 6-13) of its baculovirus IAP repeat (BIR) domain and a linker segment (residues 89-102). Here we expressed full-length human Survivin (SurF) and a series of its mutants, SurΔN7, SurΔN13, and SurΔN18 with significant truncations of the N-terminus, all of which could still dimerize in solution. Single-molecule force spectroscopy (SMFS) was used to quantitate the unbinding forces of full-length and the muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…Chem., 2011, 9, 4032-4034 | 4033 (20 mM) the non-His-tag GST showed no fluorescence recovery. Simultaneously, the His-tagged survivin 14 was also used to clarify the switch-on fluorescence response of 1/Cu 2+ to the histidine-rich protein, which show very similar result as the His-tagged GST (Fig. 5).…”
mentioning
confidence: 89%
“…Chem., 2011, 9, 4032-4034 | 4033 (20 mM) the non-His-tag GST showed no fluorescence recovery. Simultaneously, the His-tagged survivin 14 was also used to clarify the switch-on fluorescence response of 1/Cu 2+ to the histidine-rich protein, which show very similar result as the His-tagged GST (Fig. 5).…”
mentioning
confidence: 89%
“…The survivin monomer associates with borealin and inner centromere proteins to regulate chromosome segregation and cytokinesis, and the homodimer, dependent upon hydrophobic contacts at the interaction surface, has anti-apoptotic functions (Gao et al 2010). We also investigated the presumed dimerization of survivin in the yeast two-hybrid system.…”
Section: The Human Ferritin Heavy Chain (Fth1) Contains a Survivin-inmentioning
confidence: 99%
“…This technique has provided an opportunity to take the advantage of a solid linear functional polymer that can be completely compatible with solvents and substrates and at the same time having high mechanical stability and good dispersion [24]. Chemical bindings of polymer chains onto silica have been studied with various monomers, such as; styrene [25], vinyl acetate [26], acrylic acid [23], methyl acrylate [27], vinylpyrrolidone [20,24], vinylimidazole [28] and vinylpyridine [29]. In 2008 Gao et al reported the preparation of poly (4-vinylpyridine)eCu complex grafted silica and its use as a heterogeneous catalyst in oxidation reactions [29].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical bindings of polymer chains onto silica have been studied with various monomers, such as; styrene [25], vinyl acetate [26], acrylic acid [23], methyl acrylate [27], vinylpyrrolidone [20,24], vinylimidazole [28] and vinylpyridine [29]. In 2008 Gao et al reported the preparation of poly (4-vinylpyridine)eCu complex grafted silica and its use as a heterogeneous catalyst in oxidation reactions [29]. In 2009 Han et al used poly (N-vinylpyrrolidone)eRu complex grafted silica as a catalyst for hydrogenation of aromatic compounds [30].…”
Section: Introductionmentioning
confidence: 99%